Prospects for the use of metaverse tools in the field of public finance in Russia - Yu. A. Altynov (Модернизация, инновация, развитие, 2023)
Purpose: of the study is to identify promising areas for the use of metaverse technologies in the field of public finance in Russia in the context of the current sanctions restrictions and considering the peculiarities of the national budget system.Methods: the research uses such general scientific methods as literature review, comparative analysis, generalization and analysis of factual data. The work uses the method of constructing block diagrams that describe the key relationships of objects and related business processes to illustrate the proposed innovations.Results: the main results of the study include: 1) proposals for further digitalization of public and socially significant services using VR / AR technologies; 2) a scheme for integrating distributed ledger technologies (based on blockchain) into the treasury budget service system; 3)  guidelines for the use of smart contract technologies in the field of public procurement, considering exclusive and inclusive access.Conclusions and Relevance: most of the current government information systems are based on traditional relational databases, which have technological limitations compared to modern distributed ledger technologies. At the same time, the development of the sphere of public finance in the context of the digital transformation of economic relations and the active spread of metauniverses requires continuous updating of the technological infrastructure. The study made it possible to conclude that the technological capabilities of the metaverses cover the current needs for the digital transformation of public finances. In addition, for the Russian public finance sector, the current metaverse tools can be assessed as a factor in further digital development under the current sanctions restrictions.